FACTORES DE RIESGOS DE ANEMIA EN GESTANTES EN EL PUESTO DE SALUD CRUZ BLANCA SETIEMBRE-DICIEMBRE 2018 - SARAVIA HUILLCAHUA, CIELO MARGARITA (2020)
TITLE: Risk factors for anemia in pregnant women at the Cruz Blanca Health Post September-December 2018. OBJECTIVE: To determine the risk factors for anemia in pregnant women at the Cruz Blanca Health Post September-December 2018. METHODOLOGY: cross-sectional being September-December 2018, the studied population was 54 pregnant women, in the same way their sample was constituted. The instrument was a questionnaire and data collection form. RESULT: The monthly income approximates between 500 to 1000 nuevos soles (50%), having as secondary education level (70.4%), it was revealed that the parity of the pregnant women is of 1 to 2 children (38.9%). The food most consumed by pregnant women is fruits (66.7%) and chicken with (53.7%), leaving little consumption of stew with 92.6%, fish (75.9%) and red meat (53.7%). The study was carried out on 54 pregnant women, 32 of them presented anemia (59.2%), the most prevalent type of anemia was mild anemia (33.3%), no severe anemia events were evidenced. CONCLUSION: We observed that the nutritional factor generated more impact on the nutrition of the pregnant woman, occurs as a consequenceof the types of food that they consume and it was revealed that during pregnancy the pregnant women presented mild anemia. KEY WORDS: Anemia in pregnant women, risk factors.